Science of International Law and Regional Orders: A Critical Appraisal of Alejandro Alvarez and Carl Schmitt - Simonyan, Artur (Revista Tribuna Internacional, 2023)
In this article, I deconstruct the legal science of Alejandro Alvarez – a Chilean jurist – and Carl Schmitt – a German constitutional and international law scholar – to represent the normative traces of the theoretical construct of regional international law. The article revisits Schmittian grossräume theory and Alvarez's American international law as empirical evidence of normative deliberations of regionalism's functionality in international law. It then comparatively concludes that both theories that hinge on the Monroe doctrine have envisioned distinct patterns of regional international law: vertical-apologetic and horizontal-utopian. It finally elucidates the contemporary relevance of revisiting their scholarship on regional international law in the 21st century.